Analisis aktivitas projek penguatan profil pelajar pancasila (P5) peserta didik kelas iv ditinjau dari perspektif proses kreatif - Pratiwi Panca Wati; Karsono Karsono; Peduk Rintayati (Didaktika Dwija Indria, 2025)
This study aims to describe the process of P5 activities of fourth grade students of Bratan 1 Elementary School from a creativity perspective. This study uses a descriptive qualitative approach. Data collection techniques used are observation, interviews, and document studies. The subjects of this study were fourth grade students of Bratan 1 Elementary School based on purposive sampling subject selection techniques. Data were validated using source and technique triangulation. Data analysis used the Miles and Huberman model consisting of data reduction, data presentation, and drawing conclusions. The results of the study indicate that students have carried out the creative process stage in P5 activities consisting of preparation, incubation, illumination and verification stages. In the preparation stage, students collect information through various activities such as watching videos, listening to teacher explanations, asking questions, and discussing. In the incubation stage, students reflect on the information they have obtained, reread, and do activities that are not related to the project. In the illumination stage, students begin to find ideas and express them verbally and in writing. In the verification stage, students re-examine the results of their projects and ask for feedback from others.